Medicaid Utilization among Middle-age and Older Adults: A Health and Retirement Study Longitudinal Analysis (1998 to 2014). Issue 3 (4th May 2023) - Tavares, Jane; Cohen, Marc A.; Silberman, Susan; Popham, Lauren
ABSTRACT: With over fifteen million older adults in the United States relying on the means-tested Medicaid program for healthcare coverage, there has been concern over rising Medicaid costs among this rapidly growing age group. Few studies have longitudinally examined trends among older beneficiaries over time to identify factors related to Medicaid utilization and to better understand how potential coverage changes might impact this group. This study used the 1998 to 2014 waves of the Health and Retirement Study (N = 8, 162) to analyze a representative sample of those aged 50 and older to ascertain demographic, health, and economic factors associated with Medicaid utilization over a sixteen-year period. The analyses showed stable probabilities of accessing the program over time and observed that the most vulnerable older adults make up the pool of Medicaid beneficiaries. There is no evidence of significant asset divestment in order to qualify for benefits. Multivariate analyses further revealed those who were older, female, minority race/ethnicity, less educated, in poorer health, below the federal poverty line, and with lower net wealth had a higher risk of utilizing Medicaid during the observed time period than their counterparts. Findings highlight the importance of monitoring changes in the documented risk factors over time in terms of their impact on Medicaid utilization and underscore the need to consider how these factors may be interrelated.